2015
DOI: 10.1037/xhp0000032
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Arabic diacritical marks: Phonological–syntactic disambiguation of homographic verbs and visual crowding effects.

Abstract: Diacritics convey vowel sounds in Arabic, allowing accurate word pronunciation.Mostly, modern Arabic is printed non-diacritised. Otherwise, diacritics appear either only on homographic words when not disambiguated by surrounding text or on all words as in religious or educational texts. In an eye tracking experiment we examined sentence processing in the absence of diacritics, and when diacritics were presented in either modes. Heterophonic-homographic were embedded in temporarily ambiguous sentences where i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 62 publications
7
53
0
Order By: Relevance
“…However, our surveys clearly indicated that in printed modern Arabic text diacritics are mostly added to the homograph to point the reader towards one of its subordinate pronunciations in a non-constraining context (Hermena et al, 2015 subordinate diacritization pattern that would appear on the string ‫قدر‬ /qdr/ in a sentence (e.g., the noun version meaning vessel, or the verb version estimated/destined), will be the one which best fits the syntactic structure and context of the sentence. Indeed, constructing a comprehensible Arabic sentence where structure and context do not constrain the reader towards a smaller number of possible alternative pronunciations to choose from would be nearly impossible.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, our surveys clearly indicated that in printed modern Arabic text diacritics are mostly added to the homograph to point the reader towards one of its subordinate pronunciations in a non-constraining context (Hermena et al, 2015 subordinate diacritization pattern that would appear on the string ‫قدر‬ /qdr/ in a sentence (e.g., the noun version meaning vessel, or the verb version estimated/destined), will be the one which best fits the syntactic structure and context of the sentence. Indeed, constructing a comprehensible Arabic sentence where structure and context do not constrain the reader towards a smaller number of possible alternative pronunciations to choose from would be nearly impossible.…”
mentioning
confidence: 99%
“…Surveying ambiguous homographic words in Arabic and the use of diacritics in print, Hermena et al (2015) indicated that the vast majority of Arabic ambiguous homographic words are biased homographs (see e.g., Rayner & Duffy, 1986;Sereno, O'Donnell, & Rayner, 2006). Essentially, the multiple pronunciations of the Arabic homographs are not equally commonly encountered, or produced, by readers.…”
mentioning
confidence: 99%
See 3 more Smart Citations